Faktor Risiko Individu dan Masyarakat serta Gambaran Pelayanan Kesehatan terhadap Kasus Preeklampsia Berat di RSUD Manokwari Kabupaten Manokwari Provinsi Papua Barat (Periode September 2015-Februari 2016) - Endang Sri Sugiarti; Ariawan Soejoenoes; Ratnasari Dwi Cahyanti; Eddy Hartono (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2017)
Background: The high rate of maternal mortality is still a health problem in Indonesia and also reects the uality of health care during pregnancy and childbirth. The main causes of maternal mortality in Indonesia is hypertension (32.4) and postpartum bleeding (28.3). Recently in Manowari eneral Hospital there is an increase trend cases of severe preeclampsia include 12 cases (September 2015), 14 cases (October 2015) and 14 cases (November 2015).Objective: To identify ris factors of the community and health care to cases of severe preeclampsia in the eneral Hospital of Manowari, Papua Barat Province period September 2015 - ebruary 2016. Method: The study was an observational descriptive study, cross sectional design with a retrospective approach. A total of 148 medical records of pregnant women who meet the eligibility criteria for inclusion in this study. Chi-suare test and isher eact was used for statistical analysis. Multivariate analysis using logistic regression with signicance p 0.05.Result and Discussion: A total of 148 medical records of pregnant women from September 2015 - ebruary 2016 met eligibility criteria which consisted of 74 pregnant women with severe preeclampsia and 74 pregnant women without preeclampsia. Chi-suare analysis showed a signicant association between gestational age 20-36 wees with severe preeclampsia cases (p 0.016; RR 1.8; CI 1.2 to 26.6) and a history of hypertension (p 0.000; RR 2.2; CI 3.1 to 21.2). Community ris factors had no signicant relationship with severe preeclampsia. The health care services regarding severe preeclampsia was well implemented and the second phase delay mainly due to geographic factors.Conclusion: There is a signicant association between gestational age 20-36 wees and a history of hypertension in cases of severe preeclampsia.Keywords: severe preeclampsia, gestational age, history of hypertension, ris factor of the community, second phase delay